2003
DOI: 10.1359/jbmr.2003.18.12.2116
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Response to Mechanical and Parathyroid Hormone Stimulation: The Role of Mechanical Microenvironment

Abstract: Bone response under combined mechanical and PTH stimuli is important in osteoporosis. A rat tail animal model with computer modeling was used to examine bone response to loading and PTH. PTH enhances and sustains increased bone formation rate, which directly correlates to mechanical microenvironment, suggesting beneficial effects of combined PTH treatment and exercise in preventing osteoporosis.Introduction: Using an in vivo rat tail vertebra model combined with a specimen-specific, high-resolution microcomput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 56 publications
5
69
2
4
Order By: Relevance
“…These results, which are relevant to osteoblast differentiation and proliferation, indicate that vibration upregulated mRNA expression; these results are consistent with those showing the anabolic effect of mechanical stimulation on in vivo models using mammalian osteoblastic cells (Rubin et al, 1984, Turner et al, 1991, Chambers et al, 1993, Kim et al, 2003.…”
Section: Discussionsupporting
confidence: 90%
“…These results, which are relevant to osteoblast differentiation and proliferation, indicate that vibration upregulated mRNA expression; these results are consistent with those showing the anabolic effect of mechanical stimulation on in vivo models using mammalian osteoblastic cells (Rubin et al, 1984, Turner et al, 1991, Chambers et al, 1993, Kim et al, 2003.…”
Section: Discussionsupporting
confidence: 90%
“…Mechanical loading is a prerequisite for normal bone formation, as well as for preservation, and studies in rodents have demonstrated a positive synergistic effect on both cortical and trabecular bone when combined mechanical loading and PTH treatment was instituted. (29)(30)(31)(32)(33) However, the PTH exposure in those studies were intermittent and not continuous, as in PHPT, but our findings indicate that mechanical loading plays a role in the action of PTH and that mechanical stimuli are important for the effects mediated by PTH. In our study we found reduced aBMD by DXA in the forearm, spine, and hip.…”
Section: Discussionmentioning
confidence: 51%
“…The involvement of osteocytes, the primary mechanosensory cell of bone, in the anabolic effect of intermittent PTH may explain why weight bearing and intermittent PTH exert synergistic effects on bone formation [63,[100][101][102]; and why the anabolic response is greater in tibiae, which experience high mechanical strain, than in the vertebra, which experience less strain [103]. Moreover, like PTH, mechanical loading of murine bone causes a fall in the level of sclerostin [104].…”
Section: Sclerostin and Wnt Signalingmentioning
confidence: 99%